A physician-pharmacist partnership intervention for deprescribing (P3iD) among older adults attending a falls and syncope clinic: Protocol for a randomised controlled trial - Sheron Sir Loon Goh; Pauline Siew Mei Lai; Siti Nurkamilla Ramdzan; Kit Mun Tan; Amanda Mae Ching Goh; Maw Pin Tan (PLoS ONE, 2025)
Background The concept of deprescribing is gaining traction among clinicians as a formalized approach to improving medication safety for older persons. It has been found to be safe and effective in reducing medication burden. However, its implementation remains challenging. Most research has been conducted in high-income countries, with limited prospective data on deprescribing outcomes in outpatient care settings for older adults in low- and middle-income countries (LMICs). Therefore, evaluating local deprescribing interventions is essential to produce evidence on their effectiveness in older populations. Our study aimed to assess the effectiveness of the Physician-Pharmacist Partnership Intervention for Deprescribing (P3ID) among older persons attending a falls and syncope clinic. Methods This randomised controlled trial will be conducted at a teaching hospital in Kuala Lumpur, Malaysia. Participants will involve individuals aged ≥60 years with at least one chronic disease requiring pharmacological treatment, attending the falls and syncope clinic with ≥1 potentially inappropriate medication (PIM) undergoing systematic multidomain assessment and attending physicians at the clinic. The joint pharmacist-physician intervention comprises five steps: 1) PIM identification, 2) decision on cessation and prioritisation, 3) medication withdrawal, 4) monitoring and support, 5) and documentation. Conclusion The P3ID trial tests the hypothesis that a jointly led pharmacist-physician intervention in an outpatient will reduce the total number of medications, improve medication adherence, reduce falls and improve patients’ and doctors’ satisfaction towards pharmacist services. Findings from this study would inform future deprescribing practices, particularly in LMIC, pertaining to fall prevention as well as aid the development of future deprescribing interventions in other settings.